The problem of evil under the premises of pragmatism - Lima, Rodrigo César (Cognitio-Estudos: revista eletrônica de filosofia, 2017)
Evil has long been an issue completely ignored in the history of philosophy – it currently occupies the boundary between metaphysics and what is beyond mystical. Besides that, the vast majority of attempts to define evil have either failed or used theistic premises (such as the existence of God) in order to better understand it. In this paper, it shall be proposed that pragmatism could provide a better outlook on this regard, but also that if one ought to define evil one must also move away from theistic philosophies. Pragmatism could be the first step in this direction.